Antioxidant Activity and Organoleptic Quality of Salted Eggs with Pandan Leaves Addition - Khatima, Khatima; Nahariah, Nahariah; Pakiding, Wempie (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2024)
This study aimed to evaluate the antioxidant activity and organoleptic quality of salted eggs enhanced with varying concentrations of pandan (Pandanus amaryllifolius) leaf extract. A Completely Randomized Design (CRD) was employed with four treatment levels (0%, 15%, 30%, and 45%) and three replications. Antioxidant activity was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, while organoleptic properties were assessed using a standardized Likert scale. The addition of pandan leaves had a highly significant effect (P<0.01) on antioxidant activity and a significant effect (P<0.05) on IC₅₀ values. All treatments exhibited strong antioxidant capacity, with IC₅₀ values below 50 ppm. The 15% pandan leaf treatment yielded the most desirable color, texture, taste, and overall acceptance, while 45% addition produced the most favorable aroma. The findings demonstrate that pandan leaves can serve as a natural antioxidant source and sensory enhancer in animal-derived products. This research provides important evidence that using tropical herbal additives such as pandan leaves can enhance the functional quality of traditional poultry products, contributing to innovation and sustainability in livestock-based food processing. Keywords: Salted egg, pandan leaves, organoleptic quality, antioxidant activity